2020
DOI: 10.1519/jsc.0000000000003639
|View full text |Cite
|
Sign up to set email alerts
|

Training With Weightlifting Derivatives: The Effects of Force and Velocity Overload Stimuli

Abstract: Ti t l eTr ai ni n g wi t h w ei g h tlifti n g d e riv a tiv e s : t h e eff e c t s of fo r c e a n d v elocity ov e rlo a d s ti m uli

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 45 publications
0
50
0
3
Order By: Relevance
“…These findings may be explained by the inclusion of several weightlifting pulling derivatives that used loads in excess of their 1RM PC (e.g., mid-thigh pull, countermovement shrug, and clean pull from the floor) within the training program of the OL group. Previous literature suggests that using pulling derivatives in this manner may provide a greater force overload stimulus compared to training with submaximal loads [ 14 , 27 , 33 ]. Moving heavier loads from a static position with maximal intent mimics the demands of the SJ, thus allowing for greater transfer to performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings may be explained by the inclusion of several weightlifting pulling derivatives that used loads in excess of their 1RM PC (e.g., mid-thigh pull, countermovement shrug, and clean pull from the floor) within the training program of the OL group. Previous literature suggests that using pulling derivatives in this manner may provide a greater force overload stimulus compared to training with submaximal loads [ 14 , 27 , 33 ]. Moving heavier loads from a static position with maximal intent mimics the demands of the SJ, thus allowing for greater transfer to performance.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, pulling derivatives may be prescribed with loads in excess of a one repetition maximum (1RM) catching variation (e.g., mid-thigh pull and countermovement shrug [ 28 , 29 , 30 , 31 , 32 ]) to benefit force production (i.e., strength) or submaximal loads with more ballistic exercises (e.g., jump shrug and hang high pull [ 21 ]) to benefit velocity characteristics. A recent study compared the training effects of load-matched catching or pulling derivatives and weightlifting pulling derivatives that included a force and velocity overload stimulus [ 33 ]. The results of the previous study showed that training with pulling derivatives that use a force and velocity overload stimulus resulted in the greatest improvements in multi-joint isometric and dynamic strength, short sprint, and change of direction performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This practical solution for PPO prescription can be considered disadvantageous. When WPD are employed in training programs (i.e., exercises of less technical complexity) (Suchomel et al, 2014b(Suchomel et al, , 2015bSuchomel and Sole, 2017), the athletes are still required to learn and be proficient in WCD (i.e., exercises of high technical complexity) only for load prescription (Comfort et al, 2018;Suchomel et al, 2020). In other words, even when utilizing exercises with lesser technical complexity and; therefore, easier to learn and implement in training programs, athletes are still required to dedicate a significant amount of time to the learning of highly complex exercises.…”
Section: Ppo Based On the Relative Percentage Of 1rmmentioning
confidence: 99%
“…Many athletic training programs attempt to emphasize overloading the body for speed and strength gain while also avoiding the promotion of undesired mechanical adaptations. This DOI: 10.31236/osf.io/pzh8a 4 manipulation of resistance and training load has been studied thoroughly for speed training in various sports, typically by measuring sprints and jump testing for the performance outcomes (Gil et al, 2018;Girold et al, 2006;Rodriguez-Rosell et al, 2020;Suchomel et al, 2020). Previous literature has also posited that there are many options for increasing resistance and load to training exercises such as sprinting, and "the coach should use a high resistance so that the athlete experiences a large training stimulus, but not so high that the device induces substantial changes in sprinting technique" (Alcaraz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%